Pengaruh Sistem Pembayaran Listrik Online (Payment Point Online Bank) Terhadap Pengendalian Internal Kas Pada PT. PLN (Persero) DJBB - Maulana Yusup; Meidian Kurniawan (Jurnal Ekonomi, Bisnis dan Entrepreneurship, 2012)
The company has its own way in the benefit and boost profits from year to year. Gains usually obtained sourced from a network perusahaan.System activities related procedures in a comprehensive series to carry out an enterprise activity. Therefore, the service strategy very big influence on the activities of the company. With the waiters are good, it is expected there will be no diversion of the company The research objective was to determine the effect of electricity online payment system (payment points online bank) to internal control of cash at PT.PLN (Persero) Distribution West Java and Banten Distribution Office. Conventional payment systems that rely on physical cash as a payment instrument has been shifted due to advances in technology can replace conventional ways of containing the risk of endangering safety. Based on research data on the PT. PLN (Persero) Distribution West Java and Banten and discussion based on the theory, it can be concluded that the system of online payment of electricity was instrumental in supporting the effectiveness of internal control of cash, it can be seen from (1) The presence of general controls and application controls are adequate. Customers make payment through bank online payment points, (2) Reconciliation of receipt of funds receipt and bookkeeping is done regularly and directed accordingly (2) Process Online Payment System Electrical PPOB (Payment Point Online Bank) is an electricity bill payment service and other bills online real -Time. For it can be suggested that understanding is not uniform (the existence of different viewpoints of employees with regard to the value and effect of the application of the company's progress PPOB) can be removed and can eliminate the old paradigm of doing business processes PLN and increased knowledge of the mechanism of action of the system so as to improve performance and ultimately increase customer satisfaction and loyalty.